Randomised controlled trial of specialist nurse intervention in heart failure. Issue 7315 (29th September 2001) - Blue, Lynda; Lang, Elanor; McMurray, John J V; Davie, Andrew P; McDonagh, Theresa A; Murdoch, David R; Petrie, Mark C; Connolly, Eugene; Norrie, John; Round, Caroline E; Ford, Ian; Morrison, Caroline E
Abstract: Objectives: To determine whether specialist nurse intervention improves outcome in patients with chronic heart failure. Design: Randomised controlled trial. Setting: Acute medical admissions unit in a teaching hospital. Participants: 165 patients admitted with heart failure due to left ventricular systolic dysfunction. The intervention started before discharge and continued thereafter with home visits for up to 1 year. Main outcome measures: Time to first event analysis of death from all causes or readmission to hospital with worsening heart failure. Results: 31 patients (37%) in the intervention group died or were readmitted with heart failure compared with 45 (53%) in the usual care group (hazard ratio=0.61, 95% confidence interval 0.33 to 0.96).Compared with usual care, patients in the intervention group had fewer readmissions for any reason (86 v 114, P=0.018), fewer admissions for heart failure (19 v 45, P<0.001) and spent fewer days in hospital for heart failure (mean 3.43 v 7.46 days, P=0.0051). Conclusions: Specially trained nurses can improve the outcome of patients admitted to hospital with heart failure.